Implantable Drainage After Major Abdominal Surgery in Compromised Patients. Issue 4 (1990) - Andersson, Roland; Jeppsson, Bengt; Holmberg, Anna; Bengmark, Stig
Abstract : The risk of superinfection following routine abdominal drainage after major surgery is debated. Especially in patients with malignant diseases and a compromised host defense, this might be a factor increasing morbidity and mortality. During a 3-year period (1986–1988) 41 patients operated on for malignant abdominal conditions received a peritoneal catheter connected to a subcutaneous portal inserted in order to participate in a trial on postoperative intraperitoneal chemotherapy using 5- Fluorouracil. No abdominal drains were inserted. In 15 patients, the subcutaneous portal was used for evacuation of postoperative fluid accumulation within the abdomen. The mean age was 53 (range 41–70) years. Inserted catheters were used for drainage up to 14 days postoperatively. The daily amount of fluid drained varied from 20 to 2 000 ml with a mean of 610 ml/patient and day. One patient required removal of the catheter due to infection around the subcutaneous chamber. Otherwise, the catheter system was not associated with any other complications or complaints. One patient developed a postoperative left subphrenic abscess drained percutaneously by the guidance of ultrasonography, a complication that could not be attributed to the catheter system but merely to the major operation per se . An implantable device for peritoneal access thus also seem useful for drainage of postoperative fluid collection, as evaluated in this preliminary report.